Laparoscopic left lateral hepatic sectionectomy was expected to be the standard for the treatment of left hepatic lobe lesions: A meta-analysis. Issue 7 (February 2018) - Liu, Zhou; Ding, Haolong; Xiong, Xiaoli; Huang, Yong
Abstract: Background: Laparoscopic left lateral hepatic sectionectomy (LLLHS) has been widely accepted because of the benefits of minimally invasive surgery. We aimed to assess the benefits and drawbacks of left lateral sectionectomy (of segments II/III) compared with laparoscopic and open approaches. Methods: Relevant literature was searched using the PubMed, Embase, Cochrane, and Ovid Medline databases. We calculated odds ratios or mean differences with 95% confidence intervals (CIs) for fixed-effects and random-effects models. Results: The meta-analysis included 14 trials involving 685 patients. There were no statistically significant differences between LLLHS and open LLHS (OLLHS) regarding analgesia ( P = .31), pedicle clamping ( P = .70), operative time ( P = .54), hospital expenses ( P = .64), postoperative alanine aminotransferase levels ( P = .57), resection margin (95% CI –3.02–4.28; P = .73), or tumor recurrence (95% CI 0.51–3.05; P = .62). However, the LLLHS group showed significantly better results regarding blood transfusion (95% CI 0.14–0.73; P = .007), blood loss (95% CI −140.95 to −67.23; P <.001), total morbidity (95% CI 0.24–0.56; P <.01), and hospital stay (95% CI –3.84 to –2.31; P <.001) than the OLLHS group. Conclusion: LLLHS has an advantage in the hospital stay, blood loss, and total morbidity. It is an ideal method for LLHS surgery.